Science and society in modern India - Kumar, Deepak 1952- (Cambridge University Press, 2023)
The book delineates the role and place of the Western scientific discourse which occupied an important place in the colonization of India. During the colonial period, science became one of the foundations of Indian modernity and the nation-state. Gradually, the educated Indians sought to locate modern scientific ideas and principles within Indian culture and adopted those for the economic regeneration of the country. The discursive terrain of the history of science, especially in the context of a society with a very long and complex past, is bound to be replete with numerous debates on its nature and evolution, its changing contours, its complex civilizational journey, and finally, the enormous impact it has on our own life and time. The book offers a useful introduction to science, society, and government interface in the Indian context